1998
DOI: 10.2116/analsci.14.1045
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Analytical SHG Spectroscopy

Abstract: The progress of laser technology has brought extensive applications of nonlinear optical (NLO) spectroscopy to analytical fields. Especially, optical second harmonic generation (SHG), which is one of the most popular NLO phenomena, has been successfully applied to the study of interfaces (surfaces). Several fine reviews on surface SHG spectroscopies have appeared recently. The present article will concentrate on some new applications of SHG: second harmonic microscopy (SHM) for microstructural characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…In this way, the utilization of strong interactions between photons and molecules can considerably improve the sensitivity of analytical methods based on single-photon processes and can give rise as well to new analytical methods and applications for analytical sciences. In this article, our Reviews research findings for chemical measurements and applications for analytical sciences based on the following specific interactions between photons and molecules are described: (1) multi-photon ionization (MPI), [1][2][3] (2) second harmonic generation (SHG), [4][5][6][7] and (3) localized surface plasmon resonance (LSPR). [8][9][10][11] 2 Multi-Photon Ionization (MPI)…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the utilization of strong interactions between photons and molecules can considerably improve the sensitivity of analytical methods based on single-photon processes and can give rise as well to new analytical methods and applications for analytical sciences. In this article, our Reviews research findings for chemical measurements and applications for analytical sciences based on the following specific interactions between photons and molecules are described: (1) multi-photon ionization (MPI), [1][2][3] (2) second harmonic generation (SHG), [4][5][6][7] and (3) localized surface plasmon resonance (LSPR). [8][9][10][11] 2 Multi-Photon Ionization (MPI)…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] The main condition for providing secondorder nonlinearity in polymer films is the existence of noncentrosymmetry. [8][9][10] Polymers with NLO properties must possess large molecular nonlinearity as well as optical transparency at the required wavelength, good processibility, and good thermal and temporal stability. 11,12 For decades, several guest-host systems have been considered for NLO studies.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Totalinternal-reflection spectroscopy, [3][4][5][6] such as fluorescence spectroscopy (TIRF) [3][4][5] and Raman spectroscopy 6 , are the most frequently applied techniques on this subject; e.g., time-resolved TIRF was applied to observe the microenvironments of fluorescence molecules at the heptane/water interface where molecules around the interface had a low polarity or an extremely high viscosity of the microenvironment; 3 Ishizaka et al applied TIRF to calculate the thickness of the interface of carbon tetrachloride/water and 1,2-dichloroethane/water and so on, and suggested that the shape and thickness of the liquid/liquid interfaces were largely varied with the kind of solvents. 4,5 Second-harmonic generation (SHG) spectroscopy [7][8][9][10] is another technique that is highly sensitive and selective for molecules at a liquid/liquid interface; e.g., Nochi et al exhibited that SHG was applicable to alkali metal-ion recognition with the ionophore at the heptane/water, interface; also, the orientation change of the molecules at the interface was observed. 8 The polarities of water/1,2-dichloroethane and water/chlorobenzene interfaces were investigated by measuring the SH intensity of the polarity indicator molecules, which were found to be influenced by the polarity of the bulk phases.…”
Section: Introductionmentioning
confidence: 99%